Characteristics of the phyllosphere microbial community and its relationship with major aroma precursors during the tobacco maturation process - Shi, Yixuan; He, Yuansheng; Zheng, Yuanxian; Liu, Xixi; Wang, Shuzhong; Xiong, Tian’e; Wen, Tao; Duan, Hong; Liao, Xiaolin; Cui, Quanren; Nian, Fuzhao (Frontiers in Plant Science, 2024)
Numerous bacteria, fungi and other microorganisms in the tobacco phyllosphere interstellar area participate in the physiological metabolism of plants by interacting with the host. However, there is currently little research on the characteristics of tobacco phyllosphere microbial communities, and the correlation between tobacco phyllosphere microbial communities and correlated with tobacco phyllosphere trichome morphology, while Alternaria showed the opposite pattern. In conclusion, the microbiota (bacteria and fungi) and aroma precursors of the tobacco phyllosphere change significantly as tobacco matures. The presence of Acidisoma, Ralstonia, Bradyrhizobium and Alternaria in the phyllosphere microbiota of tobacco may be related to the aroma precursors of tobacco.